2008
DOI: 10.1103/physrevlett.101.216601
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic Spin Transfer Torque in High Anisotropy Magnetic Nanowires with Narrow Domain Walls

Abstract: Current induced domain wall (DW) depinning of a narrow DW in out of plane magnetized ðPt=CoÞ 3 =Pt multilayer elements is studied by magnetotransport. We find that for conventional measurements Joule heating effects conceal the real spin torque efficiency and so we use a measurement scheme at a constant sample temperature to unambiguously extract the spin torque contribution. From the variation of the depinning magnetic field with the current pulse amplitude we directly deduce the large nonadiabaticity factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
131
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(142 citation statements)
references
References 33 publications
10
131
1
Order By: Relevance
“…The interaction of spin polarized current with magnetization gives rise to various fascinating spin-torque effects such as magnetization reversal of nanomagnets in junction configurations [1][2][3][4][5] and current-induced domain wall motion [6][7][8][9][10][11]. The interest in these effects is not only theoretically motivated, but also for their expected central role in novel spintronics devices, as they offer efficient and scalable methods to control magnetic configurations on a nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of spin polarized current with magnetization gives rise to various fascinating spin-torque effects such as magnetization reversal of nanomagnets in junction configurations [1][2][3][4][5] and current-induced domain wall motion [6][7][8][9][10][11]. The interest in these effects is not only theoretically motivated, but also for their expected central role in novel spintronics devices, as they offer efficient and scalable methods to control magnetic configurations on a nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…͓doi:10.1063/1.3405712͔ Current induced domain wall motion ͑CIDM͒ in ferromagnetic nanoscale wires holds promises for applications in the field of data storage or logic devices 1,2 and was observed by a number of groups. [3][4][5][6][7] Recent studies on materials with perpendicular anisotropy have revealed a higher efficiency for CIDM than in the case of in-plane magnetized materials. [8][9][10][11] Especially the contributions of the adiabatic 12,13 and nonadiabatic spin torque due to spin relaxation [14][15][16] or momentum transfer 12,14 to the domain wall ͑DW͒ motion and their dependence on the material properties are so far not fully understood.…”
mentioning
confidence: 99%
“…At the time, most of the CIDWM results were assumed to be predominantly governed by the non-adiabatic STT because the current densities required to move the DW were much smaller than the threshold value predicted theoretically on the basis of intrinsic pinning. This raised a question on the strength of the non-adiabatic STT, but a clear consensus was not reached because of large scattering of the values of the reported non-adiabatic STT parameter β, [24][25][26][27][28][29][30] which probably originated from the complex internal DW structures. The precessional behavior of DW motion 31,32) as well as the acceleration=deceleration of DWs [33][34][35] was also presented.…”
Section: Progress In Study Of Current-induced Domain Wall Motionmentioning
confidence: 99%